1995
DOI: 10.1063/1.470361
|View full text |Cite
|
Sign up to set email alerts
|

Propensities toward C2H(Ã 2Π) in acetylene photodissociation

Abstract: When expansion-cooled acetylene is excited to the ν″1+3ν″3 vibrational level (4 quanta of CH-stretch) and then photodissociated at 248.3 nm, the dominant product channel is C2H(Ã 2Π). This differs markedly from one-photon 193.3 nm photodissociation, which provides 1200 cm−1 less energy and yields C2H(X̃ 2Σ+) as the primary product. Photodissociation at 121.6 nm yields C2H(Ã 2Π) exclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 36 publications
3
61
0
Order By: Relevance
“…The atomic hydrogen velocity distribution obtained in the photodissociation of C 2 H 2 at Lyman-R wavelength by Lai et al 6b and Zhang et al 15 showed an important contribution of small velocities associated with a production of C 2 H mainly in the excited A state. The comparison between the CH + CH reaction and the photodissociation of C 2 H 2 at the Lyman-R wavelength (121 nm) is difficult due to the lack of theoretical information about the CH + CH reaction particularly on the multiplicity of C 2 H 2 (either in singlet or triplet state) produced in the addition step (the excitation of C 2 H 2 at Lyman-R promotes C 2 H 2 in the 3R′′( 1 Π u )2 0 1 and the 2 CH + 2 CH reaction could produce 1 C 2 H 2 or 3 C 2 H 2 ).…”
Section: Resultsmentioning
confidence: 97%
“…The atomic hydrogen velocity distribution obtained in the photodissociation of C 2 H 2 at Lyman-R wavelength by Lai et al 6b and Zhang et al 15 showed an important contribution of small velocities associated with a production of C 2 H mainly in the excited A state. The comparison between the CH + CH reaction and the photodissociation of C 2 H 2 at the Lyman-R wavelength (121 nm) is difficult due to the lack of theoretical information about the CH + CH reaction particularly on the multiplicity of C 2 H 2 (either in singlet or triplet state) produced in the addition step (the excitation of C 2 H 2 at Lyman-R promotes C 2 H 2 in the 3R′′( 1 Π u )2 0 1 and the 2 CH + 2 CH reaction could produce 1 C 2 H 2 or 3 C 2 H 2 ).…”
Section: Resultsmentioning
confidence: 97%
“…This possibility is supported by vibrationally mediated photodissociation studies, 13 which have shown that vibrationally excited C 2 H 2 (X) preferentially yields C 2 H (Ã), whereas direct single-photon excitation of the ground state C 2 H 2 yields products dominated by C 2 H (X), even though the total excitation energies differ by only 1220 cm À1 . Moreover, with sufficient vibrational excitation (v…”
Section: Introductionmentioning
confidence: 88%
“…2 Figure 1 of this work suggests that, the product ratio, X to à , is Ϸ4:1, and vibrational state distributions are as shown in Table I. The photolysis of C 2 H 2 with 193 nm laser seems to result with no excitation in CH stretch, and only a modest excitation in CC mode, i.e., up to 3 ϭ1.…”
Section: A Initial Value Distributionsmentioning
confidence: 91%
“…18 -20 C 2 H radical is found to be formed in electronic states, X 2 ⌺ g ϩ1 (0 2 0) with 2 ϭ0 -7, X 2 ⌺ g ϩ1 (0 2 1) with 2 ϭ0 -5, and A 2 ⌸(0 2 0) with 2 ϭ0 -1, from photodissociation of acetylene at 193 nm. 2,21 Time-of-flight ͑TOF͒ and laser induced fluorescence studies of C 2 H, where it is produced from a precursor molecule, are carried out to analyze photofragments. 1,3,22,23 Several electronic states of C 2 are identified as a product of the photolysis, such as, X 1 ⌺ g ϩ , a 3 ⌸ u , b 3 ⌺ g Ϫ , A 1 ⌸ u , B 1 ⌬ g , and BЈ 1 ⌺ g ϩ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation